PENDIDIKAN INKLUSIF BAGI ANAK BERKEBUTUHAN KHUSUS - Kasman . (Jurnal Education and Development, 2020)
Education is a basic need of every human being to ensure his life to be more dignified. .therefore the state has an obligation to provide quality education services to each of its citizens without exception including those who have differences in ability (disability) as stipulated in the 1945 Constitution article 31 paragraph 1.the education of children with special needs becomes a challenge in the world of education, because not all schools are willing to accept children with special needs in their educational environment. the implementation of inclusive education for Children with Special Needs should be able to create an environment that is friendly, fun, flexible, can foster confidence in students and educators who have special abilities. the reality in the field of the implementation of inclusive education is not all in accordance with the guidelines for implementation, both in terms of student conditions, teacher qualifications, supporting infrastructure, parent support and support from the central and regional governments. basically the implementation of inclusive education for children with special needs is still a phenomenon